GREEN INNOVATION, RISK MANAGEMENT, CSR, AND GCiG IMPACT ON FIRM VALUE - Mochammad Rofiq Alieffudin; Tantina Haryati (Universitas Muhammadiyah Tangerang, 2026)
This study examines the effect of green innovation, risk management, and corporate social responsibility (CSR) on firm value, with good corporate governance (GCG) as a moderating variable in manufacturing companies within the consumer non-cyclicals sub-sector listed on the Indonesia Stock Exchange from 2021 to 2023. Using purposive sampling, 31 companies (93 observations) were analyzed through multiple linear regression and Moderated Regression Analysis (MRA). The results reveal that green innovation significantly and positively affects firm value (Î² = 0.141, p = 0.022), while risk management (Î² = -1.127, p < 0.001) and CSR (Î² = -0.270, p = 0.017) demonstrate significant negative effects. The moderation analysis indicates that institutional ownership successfully moderates the green innovation-firm value relationship (Î² = 0.210, p = 0.038), while independent commissioners fail to moderate any relationships (p > 0.05). Audit committee effectively moderates all three relationships: strengthening green innovation (Î² = 0.012, p = 0.005) and risk management effects (Î² = 2.034, p < 0.001), while amplifying CSR's negative impact (Î² = -2.699, p < 0.001). The model demonstrates strong fitness (F = 66.465, p < 0.001; RÂ² = 0.811), explaining 81.1% of firm value variation. These findings reveal that sustainability practices require effective governance validationâ€”audit committees with financial expertise prove most critical, while structural board independence alone proves insufficient in emerging market contexts where governance implementation remains weak.